Laboratory aid to the diagnosis and therapy of infection in the neonate - Gaetano Chirico; Cristina Loda (MDPI AG, 2011)
Despite the advances in perinatal and neonatal care and use of newer potent antibiotics, the incidence of neonatal sepsis remains high and the outcome is still severe. For years, investigators have sought a test or panel of tests able to identify septic neonates accurately and rapidly in order to obtain an early diagnosis and develop a specific effective treatment for a successful outcome. In addition to the standard procedures (blood, CSF, and urine cultures), such panels have included a combination of haematological investigations (total, differential and immature cell counts), and levels of acute-phase reactants (principally CRP and procalcitonin), and cytokines (such as IL-6 or neutrophil CD64). Furthermore, the science of proteomics and genomics has been applied to the search for biomarkers, production of protein profiles and genetic polymorphisms that can rapidly help the prediction, early diagnosis, and treatment of human diseases, but, for now, data are as yet insufficient to confirm their validity.